Time remaining:
Simplify. Show all work.

Algebra
Tutor: None Selected Time limit: 0 Hours

(2 - 5i)(-1 + 6i)

Apr 5th, 2015

(2 - 5i)(-1 + 6i) =(-2*1+(2*6i) +(5i*1)-(5i*6i)

                         =(-2+12i+5i-30i^2)

                        =-2+17i-(30*-1)

                       =-2+17i+30

                     =28+17i

Apr 5th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Apr 5th, 2015
...
Apr 5th, 2015
Mar 24th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer